Redesigning the Contours of the Future Financial System - Kodres, Laura (IMF Staff Position Notes; Staff Position Note ;, 2010)
This paper explores the private- and public-sector responses to the crisis and some of the probable outcomes. Aside from improved supervision of individual institutions, greater emphasis needs to be put on financial regulations that reflect the systemic nature of financial risks and the role that macroeconomic policies play. Global consistency of regulation and financial sector taxation will be essential to mitigate systemic risks, avoid unintended distortions, and help ensure a level playing field. This note suggests the key aspects of the future contours will likely be: ? Banks are expected to return to their more traditional function as stricter regulation will limit the risks and activities they can undertake. ? The nonbanking sector will likely have a greater competitive advantage-both in supplying credit and providing investors with nonbank services-and will thus grow. ? The perimeter of regulation will need to expand to take into account risks in the nonbank sector. ? Market infrastructure will be reinforced to protect investors and will need to provide simplicity and transparency to make risks clearer and the financial system safer. ? The global financial system is likely to be smaller and less levered than in the recent past, and could well be less innovative and dynamic, at least for a while.